Acetoclastic methanogenesis led by Methanosarcina in anaerobic co-digestion of fats, oil and grease for enhanced production of methane. (January 2019) - Kurade, Mayur B.; Saha, Shouvik; Salama, El-Sayed; Patil, Swapnil M.; Govindwar, Sanjay P.; Jeon, Byong-Hun
Graphical abstract: Highlights: The addition of fats, oil and grease enhanced ultimate methane production by 217%. Firmicutes, Bacteriodetes, Synergistetes and Euryarchaeota were greatly increased. Dominance of Methanosaeta was replaced by Methanosarcina at the end of digestion. Methane was predominantly generated through acetoclastic pathway by Methanosarcina . Abstract: Fats, oil and grease (FOG) are energy-dense wastes that substantially increase biomethane recovery. Shifts in the microbial community during anaerobic co-digestion of FOG was assessed to understand relationships between substrate digestion and microbial adaptations. Excessive addition of FOG inhibited the methanogenic activity during initial phase; however, it enhanced the ultimate methane production by 217% compared to the control. The dominance of Proteobacteria was decreased with a simultaneous increase in Firmicutes, Bacteriodetes, Synergistetes and Euryarchaeota during the co-digestion. A significant increase in Syntrophomonas (0.18–11%), Sporanaerobacter (0.14–6%) and Propionispira (0.02–19%) was observed during co-digestion, which substantiated their importance in acetogenesis. Among methanogenic Archaea, the dominance of Methanosaeta (94%) at the beginning of co-digestion was gradually replaced by Methanosarcina (0.52–95%) . The absence/relatively low abundance of syntrophic acetate oxidizers and hydrogenotrophic methanogens, and dominance of acetoclastic methanogens suggested that methane generation during co-digestion of FOG was predominantly conducted through acetoclastic pathway led by Methanosarcina .